Benefits from Laguna Lake: Perspective of Small Fisher Households - Palanca-Tan, Rosalina (Archīum Ateneo, 2020)
Fishing is considered to be the most important among the many uses of Laguna Lake, the largest lake in the Philippines and second largest in Southeast Asia. Using primary data gathered through focus group discussions, key informant interviews, and a household survey together with secondary data on revenue and cost estimates for aquaculture and catch fisheries, this paper discusses the lake’s role in the economic life of two fishing communities located along the shoreline. The study, which uses a microscopic lens to look at issues from the perspective of small fisher households instead of from that of policymakers and non-government organizations, finds that households in these lakeshore communities are engaged primarily in open fishing, which has been threatened of late by poor water quality and the consequent proliferation of water hyacinths. Only the few well-off residents of these lakeshore communities are able to construct and operate small-scale fish cages while corporations and non-resident individuals own and operate large-scale fish pens. Moreover, while open fishing contributes more to fish production value and employment than does aquaculture, the latter generates more resource rent which accrues to the very few aquaculture capitalists from outside these communities. Some suggestions for redistributing the huge fishing resource rents to poor fishing households in these lakeshore communities are thus presented in this study. The need to address the issue of lake water quality and competing uses, with a view to sustainability and poverty alleviation, is also discussed.